Sidewall design to improve lining life in a platinum smelting furnace - Eksteen, Jacques; McDougall, I. (Wiley, 2012)
The matte/slag tidal zone in a platinum smelting furnace is subject to severe process conditions which can often lead to premature failure of the lining. The MgO-FeO-Si02 slag is aggressive to refractory bricks, whilst the Ni-Cu-Fe-S matte is aggressive to water-cooled copper cooling elements, and can penetrate and sulphidize refractory bricks, particularly at the high matte temperatures often experienced in the PGM industry. A novel approach to the lining design was taken at Lonmin's new 10MW Furnace 2. An indirectly-cooled graphite ring was applied in the matte/slag tidal zone, with refractory bricks on the hot face. Thermal Finite Element modelling was conducted to determine the optimal lining design in this region of the furnace. The resistance of two graphite grades to damage by slag and matte was evaluated experimentally. The graphite lining is not wet by the matte, and is resistant to slag attack at operating temperatures. In comparison to water-cooled copper in various configurations, cooled graphite shows promise as an indirect refractory cooling system in the tidal zone area of furnaces.